CULTIVATING VEGETABLE PLANTING BENEFICIAL FOR THE HEALTH OF SDN STUDENTS WEST CILANDAK 07 SOUTH JAKARTA BY VERTICULTURE WAY - Rusdiyanto, Edi; Munawir, Abdillah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The purpose of this service is to cultivate students and teachers in schools planting organic vegetables with maximum yields on narrow school land which is beneficial for the health of students. The method used is Active and Participatory Learning with material discussions, practices and demonstrations. The results of this service provide an increase in students' and teachers' understanding of the importance of cultivating organic vegetable farming. On the other hand, being able to educate students from an early age in maintaining health by consuming organic vegetables can be done from the simplest thing, namely by cultivating organic vegetables vertically. Understanding in using this technique of providing verticulture is strengthened because only with a narrow 3 x 4 m land can cultivate vegetables with maximum yields of organic vegetable harvests. Besides being able to cultivate organic vegetable farming, the verticulture technique itself can also provide a beautiful atmosphere. So that it can spoil school students and provide a calm and comfortable atmosphere for students in the school environment.